Correction: Selective photoregulation of the activity of glycogen synthase and glycogen phosphorylase, two key enzymes in glycogen metabolism. Issue 39 (16th September 2015) - Díaz-Lobo, Mireia; Garcia-Amorós, Jaume; Fita, Ignacio; Velasco, Dolores; Guinovart, Joan J.; Ferrer, Joan C.
Abstract : Correction for 'Selective photoregulation of the activity of glycogen synthase and glycogen phosphorylase, two key enzymes in glycogen metabolism' by Mireia Díaz-Lobo, et al., Org. Biomol. Chem., 2015, 13, 7282–7288.